Interfacial plasmonic effects of gold nanoparticle-decorated graphene oxides on the performance of perovskite photovoltaic devices. (15th November 2020) - Lin, Yu-Tung; Kumar, Gautham; Chen, Fang-Chung
Graphical abstract: Highlights: Au NPs anchored on graphene oxides are synthesize and characterized. The NPs are positioned at the interface between the anode buffer and perovskite active layers. The NPs exhibit unique interfacial plasmonic effects to improve device efficiencies. The enhanced performance can be used to recover photonic energy from the artificial light sources. Abstract: Incorporation of metal nanoparticles (NPs) that can trigger localized surface plasmon resonance (LSPR) is an effective method for improving the performance of photovoltaics. Herein, Au NP- decorated graphene oxides (AuNP@GO) are synthesized and incorporated into halide perovskite photovoltaics (HPPVs) to improve their efficiencies. The resulting HPPVs exhibit enhanced power conversion efficiencies (PCEs) under illumination at 1 sun and the device enhancement can be attributed to the LSPR effects of the AuNP@GO nanocomposites. More interestingly, from the external quantum efficiency (EQE) spectra, we find two spectral wavelength regimes where the EQE values are improved. Because the Au NPs are positioned at the interface between the buffer layer and the perovskite active layer, we attribute such unique "interfacial" plasmonic effects to the fact that the Au NPs are affected by the two dielectric environments surrounding them. Because solar radiation covers a broad wavelength range, the interfacial plasmonic effects should extend the spectral range of enhanced light absorption. Further, the potential of the AuNP@GO nanocomposites to enhance the performance of HPPVs under indoor lighting conditions is also evaluated.